Innovation in emergency medicine. a perspective from a low middle income country- Pakistan - Mirza Noor Ali Baig; Walid Hussain Farooqi; Asad Mian (Journal of the Pakistan Medical Association, 2020)
In today’s world, creativity and innovation are an essential part of almost every aspect of life. From art to health care, creativity and innovation play an integral role. Even in our everyday lives, we employ creative and innovative measures to trouble shoot different hindrances. Unfortunately, no single agreed-upon definition for creativity exists. The more commonly advocated description claims creativity is “to come up with something novel and useful”. Innovation, on the other hand, has been clearly defined as “Something new, or perceived new by the population experiencing the innovation that has the potential to drive change and redefine healthcare’s economic and/or social potential.” [1] Creativity and innovation, usually go hand in hand and we believe that creativity is considered to be the process of developing or coming up with an end product which is ultimately labeled as “innovation.”